The pathosystem wheat (Triticum aestivum) root-Fusarium graminearum : complex plant responses and fungal strategies - Wang, Qing; Justus Liebig University Giessen (My University, 2015)
In the present study the F. graminearum-wheat root pathosystem has been systematically examined. This pathosystem represents a complex of Fusarium diseases including root rot (FRR), crown rot (FCR) and seedling blight (FSB). A comprehensive bioassay has been established to study and elucidate the causes and features of FRR. The bioassay combines different phenotypic evaluations and yielded consistent and significant results which prove its usefulness for resistance research and wheat breeding.The FRR bioassay combined with different microscopy techniques was applied for studies of plant-pathogen interaction. An important result of the studies was the identification of different wheat responses ranging from partial resistance to high susceptibility. Partial resistance was characterised by an impaired fungal accumulation in roots accompanied by a delayed disease spread better plant performance (biomass production, yield, etc.). This was confirmed by comparative confocal laser scanning microscopy of the partially resistant cv. Florence-Aurore and the highly susceptible Line 1105.16. Finally, the phytopathological and histopathological examinations carried out in this study allowed the definition of three distinct phases of FRR disease comprising i) root infection; ii) root colonization at infection sites; and iii) progressive root colonization accompanied with a successful disease spread. The first two phases were found to be critical for the disease establishment and therefore, provide targets for further research and selective phenotyping in the course of genetic studies and/or wheat breeding. An important outcome of this study was the discovery that upon successful root colonization, F. graminearum can enter the vascular system of the wheat stem and spread systemically to leaves and spikes without causing visible disease symptoms. Tissue-adapted invasion strategies were uncovered in which the root cortex cells, the vascular stem tissues and the leaf hairs are preferential targets for colonization. At later disease stages the stem base was increasingly used as storage for the pathogen and source for the dispersal of mycotoxins and hyphae into the developing plant, probably contributing to the frequently observed senescence of tillers and whitehead symptoms. Consequently, at later disease stages the DON mycotoxin was detected in all plant parts. Thus, FRR has the potential to affect critical growth stages, especially since both the pathogen and the toxin were detected in spikes at anthesis (flowering). Major FHB resistance genes were shown not to protect against root rot at seedling stages since even highly FHB resistant genotypes have shown a high susceptibility to FRR. Hence, there is a high risk that new elite cultivars with enhanced FHB resistance are susceptible to FRR at seedling stages. On the other side, besides features that are unique for root rot, other features of the FRR pathogenesis were reminiscent of spike colonization. The hypothesis that such similarities of the pathogens activities might be causal for similarities of wheat responses was strongly supported by the finding that partial FRR resistance is accompanied by the activation of different defence mechanisms (DON detoxification and JA-triggered basal defence) known from FHB, too. In roots the tested 12 FHB/DON resistance genes were up-regulated in the FRR resistant genotype Florence-Aurore which is, however, highly susceptible to FHB. Nevertheless, the respective expression patterns were basically similar to those in spikes by covering all phases of main infection and early colonization, indicating perception of the pathogen by the wheat root. The hypothesis that resistance against Fusarium diseases including FRR and FHB is plant age dependent has been tested in this study. This hypothesis is supported by the finding that the transition from seedling to post-seedling stages is associated with changes in wheat responses to FRR leading similar responses to FRR and FHB. In fact, upon adult root infection the early resistance of cv. Florence-Aurore turned to FRR susceptibility correlated with absent defence gene inductions. On the contrary, wheat genotypes susceptible during seedling stages showed better performances and absence of defence gene inductions. This finding is especially remarkable since it could also be demonstrate in this study that no fundamental differences exist in the course and severity of root rot after seedling and adult root infection, indicating that such infections can be a major threat even after the seedling stage. These results strongly indicate that resistance of wheat to different Fusarium diseases may not rely on the presence of different genes, but rather on transcriptional modifications related to the physiological plant age, reminiscent of adult plant resistance.

Gegenstand und Ziel dieser Arbeit war eine systematische Untersuchung des Pathosystems F. graminearum-Weizen (Triticum aestivum). Dieses Pathosystem beinhaltet einen Komplex von Fusarium-Krankheiten, die den Weizenbau erheblich beeinträchtigen können; dazu gehören die Wurzelfäule (FRR), die Kronenfäule (FCR) und die Ähren-Fusariose (FHB). Ein notwendiger, erster Schritt war die Weiterentwicklung und Anwendung eines zuverlässigen und praktikablen Bioassay für die Fusarium-Wurzelfäule, die primär unterirdische Pflanzenorgane befällt und sich einer herkömmlichen, frühen Phänotypisierung entzieht. Diese Untersuchungen zeigten das FRR mit einem breiten Schadspektrum einhergeht, das signifikante Beeinträchtigungen der Weizenentwicklung sowohl im Sämlings- als auch im Erwachsenen-Stadium zur Folge hat. Ein wichtiges Ergebnis war die Identifikation von zwei Genotypen mit partieller Resistenz gegen FRR. Ferner zeigen die Untersuchungen zur Wurzelinfektion im Sämlings- und Erwachsenen-Stadium eine inverse Reaktion des Weizens bezüglich der Wurzelfäule und Ähren-Fusariose.In einem vergleichenden Ansatz wurden die pilzlichen Strategien der Wurzel- und Pflanzenbesiedlung in der partiell resistent Sorte Florence-Aurore und der anfälligen Line 1105.16 mittels konfokaler Laser-Scanning Mikroskopie untersucht. Diese Studie ermöglichte bisher unbekannte Einblicke in die unterschiedlichen, pflanzen-gewebespezifischen Pilzstrategien, aber auch in den Charakter der Resistenz gegen FRR. Eine Resistenz des Weizens gegen die Wurzelinfektion wurde nicht beobachtet, weder im Sämlings- noch im Erwachsenen-Stadium. Tatsächlich zeigten die mikroskopischen Untersuchungen zur Wurzelinfektion bei Sämlingen, das F. graminearum, bisher als Ährenpathogen angesehen, über komplexe hyphale Strukturen zur Wurzelinfektion verfügt. Ein wichtiges Resultat der Arbeit ist die Erkenntnis, dass F. graminearum nach erfolgreicher Wurzelkolonisierung das Gefäßsystem des Weizenhalm besiedeln und sich ohne erkennbare Symptome in periphäre Organe ausbreiten kann. Wie bereits für die Wurzeln berichtet, ist auch die Ausbreitung in Halm und Blätter im resistenten Genotyp deutlich verzögert und reduziert. Während das Mycotoxin DON zunächst nur in der Wurzel nachzuweisen ist, kann es später in allen Geweben bzw. Entwicklungsstadien von Weizenpflanzen gefunden werden. Sowohl das Pathogen selbst als auch das Mykotoxin wurden schließlich zu Beginn der Blüte auch in Ähren detektiert. Für das Pathogen wurde dieses Ausbreitungspotential auch nach Wurzelinokulationen im Erwachsenen-Stadium beobachtet. Die phytopathologischen und histopathologischen Untersuchungen im Zeitverlauf ermöglichten die Definierung distinkter FRR-Stadien: i) frühe Infektion, ii) Hauptinfektion, iii) Kolonisierung der Wurzel und danach auch distaler Gewebe/Organe. Dieser skizzierte Krankheitsverlauf zeigt Ähnlichkeit mit der FHB-Pathogenese. Offenbar geht partielle FRR-Resistenz mit der Aktivierung von Abwehrmechanismen (DON-Detoxifikation und Jasmonsäure (JA)-gesteuerte generelle Abwehr) einher, die schon von FHB bekannt sind. In den Wurzeln waren FHB- bzw. DON-Resistenzgene in der FRR-resistenten Sorte Florence-Aurore hochreguliert, obwohl diese gegen FHB hochanfällig ist und alle getesteten Gene in den Ähren keine Induktion zeigten. In den Wurzeln der FHB resistenten Kultivare Sumai 3 und Ning 7840 hingegen waren die getesteten Gene nicht induziert, bzw. wesentlich später induziert. Unter den getesteten Genen erwies sich ein Zinkfinger-Transkriptionsfaktor als interessantes Kandidatengen für die Resistenzregulation. In einer vergleichenden Zeitreihenstudie zwischen Wurzel und Ähren konnte gezeigt werden, dass unterschiedliche Schlüsselgene der JA-gesteuerte generellen Abwehr sowohl im Sämlings- (FRR) als auch im Erwachsenen-Stadium (FHB) im Zusammenhang mit Resistenz induziert sind. Auch für diese Gene zeigten sich inverse Expressionsmuster hinsichtlich der Genotypen. Dies war umso interessanter als die Expressionsmuster in Wurzeln grundsätzlich denen in Ähren entsprachen: Resistenz assoziiert mit frühen und oft anhaltenden Expressionen, die typischerweise während kritischer Phasen im Krankheitsverlauf gipfeln; Anfälligkeit assoziiert mit (wesentlich) späteren und oft kurzzeitigen Expressionen. Auch die Studie zu Genexpressionen erbrachte Hinweise auf altersbedingte Änderungen in Weizenresistenz gegen Fusarium-Krankheiten. Dazu konnte gezeigt werden, (1) dass die Resistenz gegen Fusarium-Erkrankungen der unter- und oberirische Pflanzenorgane möglicherweise hinsichtlich der beteiligten Gene nicht so verschieden ist, wie bisher in der einschlägigen Forschung angenommen wird; und (2) dass sich eine quantitative Resistenz sich nicht notwendigerweise durch das Spektrum induzierter Gene von einer Anfälligkeit unterscheidet, sondern vielmehr durch den Zeitpunkt der Geninduktionen.
Das Pathosystem Weizenwurzel (Triticum aestivum) - Fusarium graminearum : komplexe Pflanzenreaktionen und Pilzstrategien
Keywords: ddc:630